Criminal Law Policy Against Law Enforcement Officers Who Commit Violence Resulting in Death from the Perspective of the New Criminal Code and Islamic Criminal Law - Annisa Putri Sinaga; Syaddan Dintara Lubis (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2026)
Indonesia, as a country based on the supremacy of law, places criminal law as an important instrument in maintaining order and protecting the right to life of the people. However, in law enforcement practices, excessive violence by officers resulting in death is still found, thus raising issues regarding legal accountability. This study was conducted to analyze the criminal law policy towards law enforcement officers who commit violence resulting in death based on the provisions of the Criminal Code (New Criminal Code) and review it from the perspective of Islamic criminal law. In contrast to previous studies which generally only examine criminal accountability from a positive legal perspective, this study combines the analysis of the Criminal Code with the study of Islamic criminal law. This study uses a normative juridical method through a statutory law approach and a conceptual approach with a literature study on related laws and regulations, legal literature, and sources of Islamic law. The results of the study indicate that law enforcement officers who commit violence resulting in death can be held accountable under Article 466 paragraph (3) of the New Criminal Code, with abuse of authority as a circumstance that can aggravate the crime as regulated in Articles 58 and 59 of the Criminal Code, and it is still possible to be subject to administrative and disciplinary sanctions. From an Islamic criminal law perspective, such acts are punishable by diyat (a type of punishment). Thus, both positive and Islamic criminal law emphasize the legal consequences for officers who commit violence that results in death.